Bronchial epithelial cell-derived prostaglandin E2 dampens the reactivity of dendritic cells - Schmidt, Lotte M.; Belvisi, Maria G.; Bode, Konrad A.; Bauer, Judith; Schmidt, Claudia; Suchy, Maria-Theresia; Tsikas, Dimitrios; Scheuerer, Jutta; Lasitschka, Felix; Gröne, Hermann-Josef; Dalpke, Alexander (The journal of immunology, 2011)
Airway epithelial cells regulate immune reactivity of local dendritic cells (DCs), thus contributing to microenvironment homeostasis. In this study, we set out to identify factors that mediate this regulatory interaction. We show that tracheal epithelial cells secrete soluble factors that downregulate TNF-α and IL-12p40 secretion by bone marrow-derived DCs but upregulate IL-10 and arginase-1. Size exclusion chromatography identified small secreted molecules having high modulatory activity on DCs. We observed that airway tracheal epithelial cells constitutively release the lipid mediator PGE2. Blocking the synthesis of PGs within airway epithelial cells relieved DCs from inhibition. Cyclooxygenase-2 was found to be expressed in primary tracheal epithelial cell cultures in vitro and in vivo as shown by microdissection of epithelial cells followed by real-time PCR. Paralleling these findings we observed that DCs treated with an antagonist for E-prostanoid 4 receptor as well as DCs lacking E-prostanoid 4 receptor showed reduced inhibition by airway epithelial cells with respect to secretion of proinflammatory cytokines measured by ELISA. Furthermore, PGE2 mimicked the effects of epithelial cells on DCs. The results indicate that airway epithelial cell-derived PGE2 contributes to the modulation of DCs under homeostatic conditions.